Incidental wandering gall bladder: a rare case report - Khurana, Ankita; Utaal, Maneshwar Singh; Ahluwalia, Anmol Singh (International Surgery Journal, 2024)
The pre-operative diagnosis of wandering gallbladder is challenging until complicated by torsion or necrosis. Ultrasonography remains the mainstay radiological investigation for gall bladder pathologies. Computed tomography can be used in complicated cases like gall bladder torsion. Free floating gall bladder may not be appreciated on ultrasonography as in our case report which has been discussed below.